Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0198352
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial factors associated with non-recovery after a minor transport-related injury: A systematic review

Abstract: BackgroundGlobally, road transport accidents contribute significantly to mortality and burden of disability. Up to 50 million people suffer a transport-related non-fatal injury each year, which often leads to long-term disability. A substantial number of people with minor injuries struggle to recover and little is known about the factors leading to poor or non-recovery. The aim of this paper is to present a systematic review of biopsychosocial factors related to poor or non-recovery after a minor transport-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…Previous research indicates differences in factors affecting recovery, yet the most commonly reported factors are high pain intensity, chronic pain, older age, pain catastrophizing, poor recovery expectations and poor pre‐accident health status . Other reasons suggested for a poor recovery, or even for permanent disability, include factors other than purely injury‐related ones.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates differences in factors affecting recovery, yet the most commonly reported factors are high pain intensity, chronic pain, older age, pain catastrophizing, poor recovery expectations and poor pre‐accident health status . Other reasons suggested for a poor recovery, or even for permanent disability, include factors other than purely injury‐related ones.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries from transport accidents are heterogeneous and recovery processes complex and challenging for patients, regardless of the type and severity of injury sustained (2,3). Multiple factors impact the recovery trajectory, including pain, poor pre-accident health state, psychological comorbidities, socioeconomic disadvantage and, in some instances, financial compensation (4)(5)(6).…”
mentioning
confidence: 99%
“…For example, in 2017 Gopinath et al demonstrated biopsychosocial factors such as general health, catastrophising, pain, social support and compensation factors were better prognostic indicators of recovery than injury type or location [22] , whilst in 2018, a systematic review by Samoborec et al concluded multiple biopsychosocial factors in uenced recovery. The strongest associations occurred between poor recovery and high initial pain intensity; pain duration, severity and catastrophising; and pre-injury physical and mental health [23] . A subsequent qualitative study by Samoborec et al in 2019 was consistent with this evidence, nding recovery was multifaceted, complex, and in uenced by comorbidities including chronic pain, depression and anxiety [24] .…”
Section: Introductionmentioning
confidence: 98%